Aesthetical decision making of music composer using ANFIS - Mashinchi, M. Reza (2007)
One aesthetical face that human is strongly surrounded by it, is music, which we are going to clarify it here. For this purpose, fuzzy logic gives us the possibility of organizing our view on this matter, due to its uncertainty and flexibility. Fuzzy rules and fuzzy reasoning are the backbone of fuzzy inference systems, which are the most important modeling tools in fuzzy set theory. They are often employed to capture the imprecise modes of reasoning that play an essential role in human ability to make decisions in environment having uncertainty and imprecision. In this paper, we use fuzzy inference system as an appropriate reasoning tool. A class of adaptive networks that are functionally equivalent to fuzzy inference systems is referred as ANFIS. We will try to use ANFIS for implementation modeling of decision making for music composing, to obtain final composed notes.